(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
This paper is dedicated to the different social conceptualization o f the terms time and work for men and women. Both time and work are essential dimensions in all of our lives, hut indeed very complicated to define and measure. They determine the lives of men and women in different ways. Strongly interconnected, the way they are presented in our societies makes them one of the main generators of inequality and discrimination between men and women. By using the existing definitions of work; working hours and leisure, this paper tends to illustrate the paradox in the estimation of the productive and reproductive work, and the time needed for their execution. That proves to be one of the main causes for the still present gender differences